Kontekstowe uwarunkowania wystąpień przysłówków stopnia w połączeniach z przymiotnikiem piękny = Contextual determinants of adverbs of degree occurrence in conjunction with the adjective beautiful - Szymańska, Monika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The subject of the analysis presented in the article are the adverbs of degree showing strong syntactic connectivity with the adjective "piękny" ("beautiful"), forming compounds with this adjective with the status of collocation. The purpose of the study - using corpus data - is to trace the contextual determinants of the occurrence of these adverbs and demonstrate the dependence of their selection on what type of object is aesthetically assessed in a given statement.
Keywords: przysłówek stopnia; kolokacja; łączliwość leksykalno-semantyczna; korpus; degree adverb; collocation; lexico-semantic collocability; corpus